2017
DOI: 10.1002/2017gl074945
|View full text |Cite
|
Sign up to set email alerts
|

Eclogitization of the Subducted Oceanic Crust and Its Implications for the Mechanism of Slow Earthquakes

Abstract: The generating mechanism and process of slow earthquakes can help us to better understand the seismogenic process and the petrological evolution of the subduction system, but they are still not very clear. In this work we present robust P and S wave tomography and Poisson's ratio images of the subducting Philippine Sea Plate beneath the Kii peninsula in Southwest Japan. Our results clearly reveal the spatial extent and variation of a low-velocity and high Poisson's ratio layer which is interpreted as the remna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Our results show that the LFE gap is located at the youngest part (~15 Myr) of the PHS slab, suggesting that the slab's lithosphere age may also affect the formation of the LFE gap. According to the results of the present study and previous works (Liu & Zhao, ; Nakajima & Hasegawa, ; Seno & Yamasaki, ; X. Wang et al, ; Z. W. Wang et al, ; Wang et al, ; Yu et al, ), we deem that the LFE gap is caused by joint effects of several factors, including the young slab age, high temperature, low fluid content, and high permeability of the overlying Eurasian plate.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results show that the LFE gap is located at the youngest part (~15 Myr) of the PHS slab, suggesting that the slab's lithosphere age may also affect the formation of the LFE gap. According to the results of the present study and previous works (Liu & Zhao, ; Nakajima & Hasegawa, ; Seno & Yamasaki, ; X. Wang et al, ; Z. W. Wang et al, ; Wang et al, ; Yu et al, ), we deem that the LFE gap is caused by joint effects of several factors, including the young slab age, high temperature, low fluid content, and high permeability of the overlying Eurasian plate.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have suggested that the LFE generation depends on the permeability of the overlying plate (Gao & Wang, ; Nakajima & Hasegawa, ) and the metamorphic dehydration of the subducting sediments and oceanic crust (Becken et al, ; Kodaira et al, ; Peng & Gomberg, ; Shelly et al, ; X. Wang et al, ). The location of slab dehydration reactions depends primarily on the temperature and pressure conditions at the top of the subducting slab and hence on the detailed thermal structure of subduction zones (van Keken et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given its depth, continuity, and gently dipping geometry, we hypothesize that the converter corresponds to the Moho of a relict slab from a past subduction event; the deeper portion of the slab likely broke off and sank into the deeper mantle, while the shallower part remained stuck in the stiff, highly viscous lithospheric mantle. Since oceanic crust generally starts to undergo transformation to eclogite at >50 km depth (e.g., Wang et al., 2017), and eclogite has seismic velocities more similar to mantle peridotite (e.g., Worthington et al., 2013), the Ps converted signal from an oceanic Moho at depth is expected to be much weaker in amplitude than that from the continental Moho, as observed. It is notable that while we seem to observe the oceanic Moho, we do not observe a corresponding NVG interface above it that represents the top of the oceanic crust.…”
Section: Discussionmentioning
confidence: 92%
“…Locations of the inter-plate boundary at depths >20 km have also been proposed based on the migration of teleseismic receiver functions 16 , and in several subduction zones the underlying low-velocity zones (LVZs) have been interpreted as the igneous oceanic crust 17 20 , including internal stratification 21 , with the downdip extent of the LVZ upper boundary consistent with thermal-petrological modelling of the basalt-eclogite transition 17 . In Cascadia, detection of an approximately coincident 3–5 km thick, landward dipping zone with anomalously high Poisson’s ratio of 0.3–0.4 has led to the proposal that the upper oceanic crust is maintained at near-lithostatic pore pressure by a low-permeability inter-plate boundary immediately above the LVZ 21 , 22 , and a similar interpretation has been made in Japan 23 , 24 . In Cascadia, however, interpretations of the inter-plate boundary using receiver functions derived from teleseismic data are systematically shallower than interpretations based on active source, e.g., normal-incidence reflection and wide-angle, seismic surveys 9 , 10 .…”
Section: Introductionmentioning
confidence: 85%